Design and development of the solar cycloidal thermal concentrator and tapered receiver assembly along with theoretical evaluation of system performance - Kulkarni, Mohan; Dingare, Sunil; Kulkarni, Chandrakant (Frontiers in Mechanical Engineering, 2023)
In this paper, design and development of solar cycloidal concentrating system along with utilization of tapered receiver is presented. For the determination of performance of the system, theoretical analysis was carried out. The novel thing of utilizing tapered receiver for solar cycloidal concentrating system is innovative approach for this research. After the determination of various parameters for this system author has filed and published a Patent having Patent No.202021028009A on 31st July 2020.For the comparative study purpose, author has taken three receivers with constant concentration ratio and having different diameters as 0.038 m, 0.031m and 0.025 m. Theoretical evaluation of system is estimated using modes of heat transfers and using the relation of energy balance. Various correlations are determined for analytical evaluation purpose. By using graphical collation of all the results for all the three receivers, author has proposed to use tapered receiver having Variable CR.